An Efficient Implementation of Distributed Storage Protocol for Large Number of Video Streams - Amrutha, B V; Jeevan, Ananya; Bhumika, R; Chaitra, P; Dhanraj, S (International Journal of Computer Sciences and Engineering, 2025)
An ever-increasing number of installed surveillance cameras, higher network bandwidth requirements and larger storage space consumption are major considerations when designing a video surveillance storage system. Traditional file systems are not tailored for receiving and storage of large scale video streams. This project attempts to present vsStor, a PB-scale, network-based video surveillance storage system which is used for storing thousands of streams. Another major characteristics of vsStor is the scale-out architecture design which allows the performance to grow by adding more hardware. We make use of clustered architecture for connecting various machines and rely on the web service mechanism for communication between them.